2009
DOI: 10.1007/s12011-009-8389-7
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Supplementation of Different Forms of Zinc in Goats on the Zinc Concentration in Blood Plasma and Milk

Abstract: The aim of the experiment was to study zinc concentration in goat's milk during a short-term oral supplementation of three organic and one inorganic form of zinc and the influence of Zn supplementation on the concentration of Zn and Cu in blood plasma. The experiment involved 31 lactating goats. The group C was the control, group L received zinc lactate, group A received zinc chelate, group T received amino acid-polypeptidic complex with zinc, and group O received zinc oxide. Zinc preparations were administere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Zinc concentration was greatly increased (P < 0.01) in milk at all stages of lactation in ewes fed 0, 15 or 30 ppm Zn. The increase of concentration of zinc in milk with supplementation of zinc is consistent with the most findings in the literature (Miller et al, 1965;Hill et al, 1983;White et al, 1991) but in the latest literature, there are different results (Pechova et al, 2009;Kirhgessner et al, 1994). However, the effects of zinc supplement on the Zn concentration in milk of ewes that are kept in intensive system has not been reported.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Zinc concentration was greatly increased (P < 0.01) in milk at all stages of lactation in ewes fed 0, 15 or 30 ppm Zn. The increase of concentration of zinc in milk with supplementation of zinc is consistent with the most findings in the literature (Miller et al, 1965;Hill et al, 1983;White et al, 1991) but in the latest literature, there are different results (Pechova et al, 2009;Kirhgessner et al, 1994). However, the effects of zinc supplement on the Zn concentration in milk of ewes that are kept in intensive system has not been reported.…”
Section: Discussionsupporting
confidence: 87%
“…Miller et al (1965) found that supplementing lactating dairy cows with 0, 500, 1000 and 2,000 ppm Zn as ZnO resulted in average milk Zn levels of 4.1, 6.7, 8.0 and 8.4 ppm, respectively. Pechova et al (2009) concluded that after 28 days of Zn supplementation, Zn concentration in milk of dairy goats was similar as at the start of the experiment in all groups. In our study, the Zn concentration in the milk of ewes fed 30 ppm additional Zn was consistently higher than that of animals fed lower Zn levels, but progressively increasing Zn levels in milk were not observed when the lower levels of Zn were consumed.…”
Section: Discussionmentioning
confidence: 82%
“…Likewise, Pechova et al. () reported that while supplementing different forms of Zn in goats during a short‐term, Zn concentration in plasma increased significantly in all administered groups, however, that in control group was unchanged. Due to homoeostatic mechanisms, supplemental Zn in diet would not increased plasma Zn concentration when Zn is adequate.…”
Section: Discussionmentioning
confidence: 85%
“…As stated in an opinion of the FEEDAP Panel (EFSA FEEDAP Panel, 2014), "with the exceptions of liver and kidney (Eisemann et al, 1979;Jenkins and Hidiroglou, 1991;Cao et al, 2000;Gallaher et al, 2000;Wright and Spears, 2004;NRC, 2005; see also review of Schlegel et al, 2013), zinc concentrations exceeding the requirements up to about 200 mg/kg feed will not result in a change of zinc concentrations in animal tissues and other products including milk (Schwarz and Kirchgessner, 1975;Miller et al, 1989;Wiking et al, 2008;Peters and Mahan, 2008;Peters et al, 2010)". This is supported by studies on zinc deposition in eggs (Mabe et al, 2003;Huyghebaert et al, 2006;Plaimast et al, 2008;Bahakaim et al, 2014) and milk (Kirchgessner et al, 1994;Pechova et al, 2006Pechova et al, , 2009 carried out on animals fed diets supplemented with sources of amino acid chelated with this trace element. This is supported by studies on zinc deposition in eggs (Mabe et al, 2003;Huyghebaert et al, 2006;Plaimast et al, 2008;Bahakaim et al, 2014) and milk (Kirchgessner et al, 1994;Pechova et al, 2006Pechova et al, , 2009 carried out on animals fed diets supplemented with sources of amino acid chelated with this trace element.…”
Section: Metabolic and Residue Studiesmentioning
confidence: 88%